Endoscopic Anatomy of the Third Ventricle Microsurgical and Endoscopic Approaches - Seeger, Wolfgang (Springer Vienna : Imprint: Springer, 2006)
In this atlas anatomical aspects important for combinations of microsurgical and endoscopic approaches are presented and illustrated. Modern imaging techniques are necessary for the three-dimensional orientation but do not show enough details for endoscopic interventions. The small visual fields need a combination of the depiction of fine details and of the three-dimensional presentation of large areas. Furthermore, problems with little known anatomical standard variants of the target areas may arise. Therefore, numerous common anatomical variants are demonstrated with reference to their impact for the surgical technique. The basis for Professor Seeger's well known drawings have been anatomical preparations, cadaver dissections and intraoperative pictures. The correct proportions are derived by measuring the distances of anatomical landmarks of cranial preparations and from CT and MR Images. The concise text supports the understanding of the anatomical figures.